Analysis of Physiological Workload in Tofu Production Process Based on Energy Recovery at Rest - Hakim, Luqman; Sulaiman; Yafi, Muhammad Mansur (Journal of Research and Technology, 2023)
UD. Koder is a manufacturing company that processes raw materials into finished products in Sidoarjo. The production process is one of UD's production processes. Koder is still with manual performance. Manual production processes with flexible body movements and a lot of physical loads still depend on the ability of workers and require human labor. The assessment of the level of physical workload of workers is not clear. The purpose of this study was to examine the categories of physical stress on workers in manual production processes using physiological methods. The method used is to measure heart rate at work and at rest, as well as evaluate worker psychology in the form of consideration of heart rate reserve (%HRR), cardiovascular load (%CVL), and energy expenditure factor (KE). The results showed that the amount of energy expenditure for each worker included Faris (7.0 Kcal/minute), Muit (4.7 Kcal/minute), Budi (4.4 Kcal/minute), Gito (4.9 Kcal/minute), Sudar (5.0 Kcal/minute), Dito (4.6 Kcal/minute), Joni (4.9 Kcal/minute) resulting in an item of average energy expenditure (5.1 Kcal/minute) where all workers were at a moderate level. The recommended improvement for production workers is that the rest time is 1 minute 27 seconds each time the process is continuous.